Asset management : whole-life management of physical assets - Lloyd, Chris, 1959- (Thomas Telford, 2010)
The insights, experience and advice of a panel of leading thinkers and practitioners from a wide range of sectors, providing readers with multiple perspectives on the practicalities of adopting asset management principles and equipping them with the tools and framework required to implement effective asset management strategies and cultures within their own organisations.